FACTORS OF THE EDUCATION SYSTEM OF THE REGION - O. Erashova (Вестник университета)
The development strategy of socio-economic system is determined by how the system is able to receive from the external environment and the resources it needs to promote the products in the environment of their livelihoods, so the identification of the whole complex of environmental factors is an important task for the regional education system. The article defines the basic building blocks of the factors of the region's education system and describes their internal content, that allows to form a strategic perspective and develop the basic content of the education system development strategy in the region.